2021
DOI: 10.3389/fcimb.2021.598672
|View full text |Cite
|
Sign up to set email alerts
|

The Fecal Microbiota Is Already Altered in Normoglycemic Individuals Who Go on to Have Type 2 Diabetes

Abstract: ObjectiveMounting evidence has suggested a link between gut microbiome characteristics and type 2 diabetes (T2D). To determine whether these alterations occur before the impairment of glucose regulation, we characterize gut microbiota in normoglycemic individuals who go on to develop T2D.MethodsWe designed a nested case-control study, and enrolled individuals with a similar living environment. A total of 341 normoglycemic individuals were followed for 4 years, including 30 who developed T2D, 33 who developed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 43 publications
(28 reference statements)
4
40
0
Order By: Relevance
“…This of course would need to be explored more deeply, for example by evaluating subjects’ feces metabolome. Changes in methane metabolism, glycosaminoglycan degradation and carbon fixation pathways in procaryotes were all found to be increased in T2D patients and in patients who later developed T2D in the study by Wang et al ., 47 which concordant with our current findings.…”
Section: Discussionsupporting
confidence: 94%
“…This of course would need to be explored more deeply, for example by evaluating subjects’ feces metabolome. Changes in methane metabolism, glycosaminoglycan degradation and carbon fixation pathways in procaryotes were all found to be increased in T2D patients and in patients who later developed T2D in the study by Wang et al ., 47 which concordant with our current findings.…”
Section: Discussionsupporting
confidence: 94%
“…However, the causality between gut dysbiosis and T2D remains enigmatic. A recent study showed that subjects that went on to develop T2D already presented a distinct GM composition prior to the dysregulation in glucose homeostasis [ 12 ]. Besides, another study reported that GM composition changes during the course of the T2D, since subjects with PreD presented microbiota features different from those observed in healthy individuals or those with T2D [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective study in the same year, 341 samples were assessed. Lower abundances of Bifidobacterium longum, Coprobacillus unclassified , and Veillonella dispar and higher abundances of Roseburia hominis, Porphyromonas bennonis , and Paraprevotella unclassified were found in diabetic patients [ 14 ]. Although many studies have been reported, most studies have reported only the intestinal flora associated with diabetes and did not clarify the importance of intestinal microbes in the occurrence and development of diabetes.…”
Section: Introductionmentioning
confidence: 99%